Refugee Shelter on Selayar Island, South Sulawesi - Amanda Apriani (Journal Research of Social Science, Economics, and Management, 2023)
Refugee shelters are a crucial asylum in restoring the physical and psychological situation. Although Indonesia is a strategic stopover country for refugees, refugee shelter facilities in the country are still far from international eligibility standards. South Sulawesi, the province with the second highest number of refugees in Indonesia, currently does not have a shelter to accommodate the diverse needs of refugees. Therefore, the purpose of this design is to design a refugee shelter in South Sulawesi that complies with international eligibility standards and can meet the needs of refugees and make it easier for the government to control. To meet this goal, data collection was conducted through a literature review of existing international refugee shelter standards and precedent building. After that, a site analysis is carried out to produce a building shape that is in accordance with the condition of the site. The result of the design is a refugee shelter that can complete architectural and non-architectural aspects including characteristics, basic needs, and evacuation activities.